MICRO, SMALL AND MEDIUM ENTERPRISES (MSME) DEVELOPMENT STRATEGY IN LAM DURO VILLAGE - Vivi Silvia; Muhammad Jamil; Muhammad Hafidhillah (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2024)
Micro, Small and Medium Enterprises (MSMEs) are productive businesses owned by individuals or groups which aim to increase and sell these products, it seems like things in a village where these MSMEs really help the economic strength of the people in the village and are driven under the cooperative or the party that manages the business, because there is a business, it is necessary to The method that will be used by researchers is using primary data and secondary data. Efforts to develop SMEs need concepts, broad knowledge so that buying and selling increases so that people will make changes in this modern era.Keywords: Cooperative, bussines using primary data, secondary data, increasing and selling production results